Pembuatan Game 2d Ilmu Tajwid “Qur’an Harmony Challenges” - Muhammad Miftahul Nur Safitri; Farandika Metandi; Agusdi Syafrizal (JURNAL VOKASI TEKNIK, 2024)
This research, titled "Development of the 2D Tajwid Game 'Quran Harmony Challenge'," aims to enhance students' interest and engagement in learning the Quran and Hadith at Madrasah Tsanawiyah Nurul Islam, Kecamatan Palaran. Addressing the issue of low student interest, the game was developed using the Multimedia Development Life Cycle (MDLC) method with Unity as the platform, and Corel Draw and Adobe Photoshop for creating graphic assets. Testing was conducted in two phases: alpha testing to ensure there were no bugs or errors and that all features functioned correctly, and beta testing involving students to evaluate the game and provide feedback using a questionnaire with Likert scale calculations. The test results indicate that this game effectively increases students' learning interest, making it an enjoyable and beneficial educational medium.